LARANGAN PENGASINGAN TANAH DAN PELUANG INVESTASI ASING DI INDONESIA - FX Sumarja (Jurnal Media Hukum, 2014)
Throughout the political history, agrarian law in Indonesia recognize the prohibition of land alienation. Foreigners or  foreign  legal  entities  (foreign  investors) were  banned  for  land  ownership.  Argrarian  Fundamental  Lawsstipulates that foreigners domicile in Indonesia and foreign legal entities which have representatives in Indonesia are  only  allowed  to have  land  use  rights  and  building  lease  rights.  In  practice,  foreigners  and  foreign  legalentities prefer  to  acquire  land  ownership  rights by nominee. Whereas  nominee  is  illegal  and  has  very weak legal position. Article 16 paragraph (1) letter h junto Article 24 Argrarian Fundamental Laws open the opportunitiesfor foreign investors  in land tenure through Guna Bangun Serah rights, by positioning the ground as a means of production  rather  than as an  investment. Guna Bangun Serah  in  Indonesia was marked by the birth of  theMinister of Finance of  the Republic of Indonesia Decree No. 470 / KMK.01  / 1994 on Procedures for Removal and Utilization of Assets  / Country’s Wealth, which adopted  the  “Turgut’s Formula”, namely  the construction and management of dams on the river Syehan Turkey.This study aims to find an alternative land ownership for foreign  investors that  require  land as  ingredients, considering  the  limited  tenure  in  Indonesia  to consider  theexpediency  of  justice  and  legal  certainty.  The  new  paradigm  is needed  in  attracting  foreign  investment  in Indonesia, in order to obtain the benefit, justice and legal certainty, through Bangun Guna Serah rights. Article 16 paragraph (1) letter h Argrarian Fundamental Laws stipulates the other rights that are not included: Properties, Cultivation  rights, Building  rights,  Tenure  and Rental  Rights will  be  established  by  law.  Bangun Guna  Serah rights defined as rights to construct a building and / or its facilities on land that is not his own and then utilize the building and  / or  its facilities  in a  certain period of  time that has been agreed, as  in  the  future the  land, buildings  and  / or  the  following  facilities will be  transfered  to  the owner of  the  land after  the  term expired. Guna Bangun Serah  rights  can be  incorporated into  the Land Bill.